COMPETÊNCIAS, ORGANIZAÇÃO E ATUAÇÃO DA JUSTIÇA FEDERAL, NO DISTRITO FEDERAL, DURANTE O PERÍODO DE 1890 A 1937 - Ronald Kruger Rodor (TRF2, 2020)
The present article aims to describe how the Federal Justice was organized and developed in the capital Republic during the period from 1890 to 1937, with a special focus on the type of lawsuit that was concretely submitted to the jurisdiction of that institution, from the analysis of the indexation of historical processes of the Judicial Section of Rio de Janeiro, and by examining the news of periodicals of the time that reported matters related to the Federal Judiciary.